Comparison of the Effect of Perchlorine, Sodium Hypochlorite, and Electrochemical Method on Disinfection of Vegetables - Hassan Hashemi (Journal of Environmental Health and Sustainable Development, 2017)
Introduction: Many vegetables are eaten raw which can lead to the prevalence of food borne diseases if not properly sanitized. The aim of this study was to compare the effect of chlorine, bleach and multioxidant solution in disinfection of edible vegetables. Materials and Methods: In this experimental study, 100 g of vegetables (lettuce, basil and mint) was disinfected by sodium hypochlorite, chlorine, and multioxidant solution at a concentration of 200 mg/L in 5, 10,15 and 20 min. Microbial load analysis was performed using SPSS-20 software with paired t-tests and ANOVA. Results: Coliforms reduction in mixed vegetables using chlorine, sodium hypochlorite and electrochemical solution were 1.07-1.47, 0.67-1.39 and 2.17-2.47, respectively. For lettuce, coliforms were reduced to 0.77-1.47, 0.57-1.33 and 2.17-2.43 log/100g. After disinfection of mint using chlorine, sodium hypochlorite and electrochemical solution, coliforms were reduced to 1.07-2.17, 0.95-1.77 and 2.47 log/100g and after Basil disinfection, coliforms were reduced to 0.87-1.87, 0.83-1.39 and 2.47 log/100g, respectively. Conclusion: With increasing concentrations of disinfectants dose, inactivation of bacteria was done in less time. Electrochemical method is the suitable option to disinfect vegetables at home and emergencies.